Congenital renal anomalies detected in adulthood - Muttarak M. (2017)
Objective: To document the types of congenital renal anomalies detected in adulthood, the clinical presentation and complications of these renal anomalies, and the most useful imaging modality in detecting a renal anomaly. Materials and methods: This study was approved by the institutional review board and informed consent was waived. Between January 2007 and January 2011, the clinical data and imaging studies of 28 patients older than 18 years diagnosed with renal anomaly at the authors' institution were retrospectively reviewed. Renal anomalies in this study included only those with abnormality in position and in form. Results: Of these 28 patients, 22 underwent imaging studies and their results constituted the material of this study. Of the 22 patients, 14 had horseshoe kidneys (HSK), four had crossed renal ectopia and four had malrotation. Sixteen patients were men and six were women. The patients ranged in age from 19 to 74 years (mean age 51.1 years). Clinical presentations were abdominal pain (13), fever (13), haematuria (4), palpable mass (2), asymptomatic (2), polyuria (1) dysuria (1), blurred vision (1), and headache with weakness of left extremities (1). Imaging studies included abdominal radiograph (15), intravenous pyelography (IVP) (8), retrograde pyelography (RP) (4), ultrasonography (US) (7), and computed tomography (CT) (9). Associated complications included urinary tract stones (17), urinary tract infection (16), hydronephrosis (12), and tumours (2). Abdominal radiograph suggested renal anomalies in nine out of 15 studies. IVP, RP, US and CT suggested anomalies in all patients who had these studies performed. However, CT was the best imaging modality to evaluate anatomy, function and complications of patients with renal anomalies. Conclusion: HSK was the most common renal anomaly, with abdominal pain and fever being the most common presentations. UTI and stones were the most common complications. IVP, RP, US and CT can be used to diagnose renal anomalies but CT is the best imaging modality to evaluate renal anatomy, function and its complications. © 2012 Biomedical Imaging and Intervention Journal. All rights reserved.